Macroinvertebrate Functional Trait Responses to Chemical Pollution in Agricultural–Industrial Landscapes. (29th September 2016) - Pallottini, M.; Cappelletti, D.; Fabrizi, A.; Gaino, E.; Goretti, E.; Selvaggi, R.; Céréghino, R.
Abstract: Both physical–chemical and biological indicators are used to assess the ecological health of ecosystems. The functional trait composition of communities has the potential to predict the impact of environmental change on ecosystems, yet, we miss evidence that information on pollution can be used to forecast the functional responses of freshwater communities. We used chemical and ecological data collected in the Nestore river basin (Central Italy) to test whether (i) there are generalities in the response of macroinvertebrate functional diversity to river pollution; (ii) water pollution filters certain functional traits and (iii) traits do better than chemical analyses at revealing ecological stress in rivers. Due to interactions with hydrology, chemical variables showed higher seasonal variation at impacted sites, so occasional water samples represented snapshots. Functional traits did well at detecting water pollution by various chemicals, and there was a clear shift of trait combinations from unimpacted to impacted sites. Anthropogenic disturbances homogenized benthic communities in terms of taxonomic and functional composition, both in space (impacted sites) and time (seasons). Traits related to feeding habits (mainly reliance on fine particulate organic matter) and tolerance to organic pollution were prevalent at impacted reaches, and functional trait compositions were more stable than water chemistry over seasons because they integrate environmental conditions over longer time periods. Functional traits can play a relevant role in the bioassessment of polluted river ecosystems, even under low to moderate disturbance. Trait‐based assessment can be complemented by chemical analyses, notably at highly polluted sites where biological diversity drops to its lowest levels. Copyright © 2016 John Wiley & Sons, Ltd.